Development of an ultrasensitive IR sensor using ZnO/SiNWs hybrid nanostructure. (2022) - Singh, Pooja; Kumar, Avshish; Dhasmana, Hrishikesh; Verma, Abhishek; Kumar, Amit; Jain, V.K.
Abstract: In this work, we report a new class of infrared (IR) photodetectors in near IR region comprising of zinc oxide (ZnO) nanoparticles − silicon nanowire (SiNWs) hybrid nanostructure. SiNWs on p-Si (1 1 1) substrate were synthesized by metal assisted chemical etching (MACE) whereas ZnO nanoparticles were prepared using green synthesis technique accompanied by the deposition of these ZnO nanoparticles over SiNWs. The fabrication ZnO/SiNWs hybrid nanostructure was characterized by using scanning electron microscope (SEM), UV–Visible spectrophotometer and X-Ray diffractometer (XRD). The NIR photo sensing response of ZnO/SiNWs were measured by using the radiation wavelength of 1064 nm at room temperature wherein it showed a large photoresponse under this illumination. The photo-resistive response of ZnO/SiNWs hybrid nanostructure was observed to be very fast (3 s) wherein ∼ 12% decrease in the initial resistance was observed under NIR illumination. As we turn off IR source, the sensor reached to its initial state within 3 s. The sample was checked continually for three on/off sets of illumination with regular interval of 30 s. Hence, the reported work is extremely promising for further development of highly efficient miniaturized NIR detectors with novel characteristics.